Impact of fin length on threshold voltage modulation by back bias for Independent double-gate tunnel fin field-effect transistors. (September 2015) - Mizubayashi, W.; Fukuda, K.; Mori, T.; Endo, K.; Liu, Y.X.; Matsukawa, T.; O'uchi, S.; Ishikawa, Y.; Migita, S.; Morita, Y.; Tanabe, A.; Tsukada, J.; et al.
Highlights: Following the review's comments, we modified the submitted paper. The I d – V d characteristics of the double gate mode were added inFig. 2 . The new references (Refs.[6–10] ) related to TFETs were added. The fin thickness changed with the fin length. We modified the figure and the caption inFig. 8 and modified the sentence in the paper. Abstract: We investigated the impact of fin length ( T fin ) on the threshold voltage ( V th ) modulation by back bias ( V b ) for independent double-gate (IDG) tunnel fin field-effect transistors (tFinFETs). It was found that V th can be tuned by V b for IDG tFinFETs regardless of T fin, which can be explained by the back-gate-effect model of IDG FinFETs. For IDG tFinFETs, the slope (back-gate-effect factor ( γ )) of V th with respect to V b increases with thinning T fin . This means that T fin thinning is effective for tuning V th by V b for IDG tFinFETs. Furthermore, it was demonstrated that this back-bias-effect is consistent with the results of device simulation using an advanced nonlocal band-to-band model.